Biomass and Carbon Mass Allometric Equation Models of Avicennia marina (Forsk.) Vierh. Case Study Pulau Dua Natural Reserve Banten PERSAMAAN ALOMETRIK BIOMASSA DAN MASSA KARBON Avicennia marina (Forsk.) Vierh. Studi Kasus Cagar Alam Pulau Dua Banten - Tyas Ayu Lestari; Aswin Rahadian; M. Yanuar J. Purwanto; Ietje Wientarsih (Jurnal Silvikultur Tropika, 2016)
Research measurements of carbon stocks Avicennia marina has been done by Dharmawan and Siregar (2008) with a DBH 5 cm. Calculation of carbon stocks Avicennia marina with DBH less than 5 cm hadn’t been done. Currently, approaches to measuring biomass and carbon mass mangrove species is being developed through allometric equation. Allometric equation to estimate carbon stocks are still limited, especially for mangrove with DBH less than 5 cm. Therefore, this research carried out calculations to obtain allometric equations for estimating biomass and carbon mass Avicennia marina with DBH less than 5 cm. The results of research can complement allometric equations that have been published previously. Allometric equations constructed using two equations, namely linear and logarithmic with two variables such as total height (x1) and diameter at breast height / DBH (x2). Allometric equation to estimated total biomass, root, stem, branch and leaves are Log YTotal = -7.92 + 2.02 Log (Tt), Log YRoot = -8.37 + 1.94 Log (Tt), Log YStem = -8.83 + 1.99 Log (Tt) + 0.419 Log (DBH), Log YBranch = -8.63 + 2.01 Log (Tt), dan Log YLeaves = -7.73 + 1.63 Log (Tt). Allometric equation to estimated total carbon root, stem, branch and leaves are Log YTotal = -8.82 + 2.21 Log (Tt), Log YRoot = -9.11 + 2.04 Log (Tt), Log YStem = -8.89 +2.06 Log (Tt) + 0.467 Log (DBH), Log YBranch = -9.41 + 2.13 Log (Tt), dan Log YLeaves = -8.46 + 1.64 Log (Tt).Key words: Seedling, stake, total height, diameter at breast height